EFFECT OF 14 POINTS ACUPRESSURE ON UPPER AND LOWER EXTREMITY MUSCLE STRENGTH LEVELS IN PATIENTS WITH NON-HEMORRHAGIC STROKE - Lalu Hersika Asmawariza; Suharyo Hadisaputro; Mardiyono Mardiyono; Desak Made Wenten Parwati (Belitung Raya Foundation, Indonesia, 2018)
Background: Acupressure is considered as one form of holistic therapies that can improve tissue perfusion to improve motor function in patients with stroke.Objective: To analyze the effect of 14 points acupressure on upper and lower extremity muscle strength in patients with non-hemorrhagic stroke patients.Methods: This was a quasi-experimental study with pretest posttest control group design. Paired comparative analytic design was also used. Thirty-eight participants were selected, which 19 participants assigned in the experiment and control group. The Medical Research Council (MRC) scale was used to measure the lower and upper muscle strengths.Results: There was a significant difference between the improvement of the upper muscle strength in the experimental group and the control group at day 3, 4, 5, 6, 7 (p = 0.010, p = 0.000, p = 0.000, p = 0.000, p = 0.000); and there was a significant difference between the improvement of the lower extremity muscle strength in the experimental group and the control group at day 3, 4, 5, 6, 7 (p=0.023, p=0.000, p=0.000, p=0.000, p=0.000).Conclusion: The 14 points acupressure is effective in increasing upper and lower extremity muscle strength in patients with non-hemorrhagic stroke.